PENERAPAN MODEL STUDENT TEAMS ACHIEVEMENT DIVISION DALAM PEMBELAJARAN MATEMATIKA - Yoseph Pius Kurniawan Kelen (KH. A. Wahab Hasbullah University, 2016)
The title of this study is: “The Implementation of Model Student Teams Achievement Division in Mathematics Learning”, made on the basis of the problem, that is: 1) the less of competition among students, 2) the influence of surroundings, the social media, parrents in the learning process of students, 3) less of student interest in learning math, 4) student’s behavior that always dependence by teachers and friends was very high. Students with lower achievements usually more pasive in learning process than students wich have high achievements. As a consequence, students with low achievement is often no attempt to study harder, so it can be one cause of student’s unfinish in study. Under these conditions, the problem in this research is how the students’ mathematics learning outcomes by implementing model Student Teams Achievement Division (STAD)? The purpose of this research is to know the students’ mathematics learning outcomes by implementing model type Student Teams Achievement Division (STAD). The kind of this research is Classroom Action Research (CAR). The subjects were students of class X AK 2 SMK Katolik Kefamenanu with many students in class is 11. Media used in collected the data in this research are question sheet and observation sheet. This research done in two cycle using the indicator of success is 70%. The results showed that cooperatif learning model of the type Student Teams Achievement Division can improve students’ mathematics learning outcomes in the class X AK 2 SMK Katolik Kefamenanu school year 2015/2016. It is seen from the precentage of completeness class in each cycle: the first cycle is 64,70% and the second cycle is 82,35%. Therefore, the writer concluded that the implementation of cooperatif learning model of the type Student Teams Achievement Division can improve students’ mathematics learning outcomes. Keywords: Implementation, Cooperative Learning Model Type Student Teams Achievement Division, Achievement of Mathematics Learning